Wage risk and portfolio choice: The role of correlated returns - Johannes König; Maximilian Longmuir (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
From standard portfolio-choice theory it is well-understood that background risk, overwhelmingly due to wage risk, is one of the central determinants of individuals' portfolio composition: higher background risk reduces risky investments. However, if background risk is negatively correlated with financial market risk, higher background risk implies more risky investment. We quantify the influence of wage risk on German investors' financial portfolio shares and find that an increase of the residual variance of wages by one standard deviation implies a reduction of the financial portfolio share by 3 percentage points. We do not find that the correlation of wage risk with financial market risk has a significant impact on portfolio choice and provide evidence that this may be due to a lack of salience.
Keywords: D12; D14; D31; 330; Background Risk; Portfolio Choice; Household Portfolios; Investment Behavior